Eating pattern and low-purine diet adherence among patients with gout arthritis - Elida Sinuraya; Antonij Sitanggang; Flora Sijabat (Malahayati International Journal of Nursing and Health Science, 2021)
Background: Eating pattern of gout arthritis patients will determine the amount of uric acid levels in their body. Adherence to a purine diet is one of the efforts made to prevent recurrence or assist healing on gout arthritis patients.Purpose: To determine the relationship between eating pattern based on type of food and adherence to purines diet in gout arthritis patients and the relationship between eating patterns based on eating frequency and adherence to purines diet in gout arthritis patients.Method: This descriptive analytic study with a cross sectional approach. The population in this study about 40 patients and the sample was taken using accidental sampling technique. The sample size was calculated by using the Yamane Taro formula so that the results were 36 participants. Questionnaires were used for data collection and the data were analyzed by using Pearson correlation with 95% confidence level (CI) with p value <0.05.Results: base on the statistical analysis, the result of this study is that there is no relationship between eating pattern based on diet based on type of food and adherence to purines diet in gout arthritis patients with p value 0.381 (> 0.05) and there is a relationship between eating pattern based on eating frequency and adherence to purines diet in gout arthritis patients with p value 0.002 (< 0.05).Conclusion: There is no relationship between eating pattern based on type of food and adherence to purines diet in gout arthritis patients and there is a relationship between eating patterns based on eating frequency and adherence to  purines diet in gout arthritis patients.